Analysis of Inpatient Registration Information System on The Timeliness of Inpatient Services at Hamba Regional Hospital - 'Aini, Qurrota; Yunengsih, Yuyun; Pasaribu, Johni S. (Publikasi Indonesia, 2025)
This research aims to evaluate the inpatient registration information system at RSUD Haji Abdoel Madjid Batoe. This research is a descriptive qualitative research with the research respondents being inpatient registration admission officers at RSUD Haji Abdoel Madjid Batoe. This research is a qualitative research using the scrum method. Findings from interviews with admissions officers showed several factors affecting the timeliness of registration, including human resource shortages, delays in procurement of materials, suboptimal procedures, slow computer systems, and limited funding. The analysis resulted in recommendations for improvement, additional staff, improved technological equipment, material and fund management, and consistent implementation of SOPs. In addition, regular training and evaluation for staff is required to ensure that procedures are followed correctly and efficiently.